Thermal and Mechanical Shock Testing of a Brick Wall and A Polystyrene Wall - Abderrahmane Khechekhouche; Bassou Karima; Khatraoui Seif Eddine; Labidi Sara (Universitas Pendidikan Indonesia (UPI), 2023)
Polystyrene is one of the many novel materials being developed today. The goal of our research is to demonstrate that polystyrene is a good construction material in the El Oued region of Southeast Algeria. It can also be a strong rival for other building materials like brick. The results of our research, particularly in thermal testing, are very promising. Polystyrene is a better insulator than brick; the temperature of the polystyrene chamber varies between 26 and 27°C, whereas the temperature of the brick chamber varies between 36 and 37 °C. Polystyrene has a 5 times mechanical impact compared to brick. Despite its lack of availability in the region's markets, polystyrene is a strong rival to other materials such as brick.